Non-Surgical Camouflage Treatment of a Skeletal Class III Patient with Anterior Open Bite and Asymmetry Using Orthodontic Miniscrews and Intermaxillary Elastics - Ye-Ji Seo; Jae Hyun Park; Na-Young Chang; Jong-Moon Chae (Applied Sciences, 2023)
This case report presents the non-surgical orthodontic camouflage treatment of an 18-year-old male patient with skeletal Class III asymmetry and severe anterior open bite. The anterior open bite was corrected by extrusion of the maxillary and mandibular anterior teeth and clockwise and counterclockwise rotation of the maxillary and mandibular occlusal plane, respectively, using intermaxillary Class III elastics between the maxillary posterior buccal miniscrews and mandibular canines and anterior vertical elastics between the maxillary and mandibular canines. Class III dental relationships and dental asymmetry were corrected via unilateral distalization of the mandibular dentition on the left side using a closed coil spring between the buccal shelf screw and hook. The patient’s smile esthetics and dental relationship were improved with a more favorable facial profile, and facial asymmetry was slightly alleviated after orthodontic camouflage treatment. The total treatment time was 15 months. A modified wraparound retainer with a scalloped labial bow, tongue crib, and tooth positioner was used simultaneously to prevent the potential relapse.